Thermal Tolerance of Horned and Polled Bali Cattle to High Ambient Temperature and Exercise Provision - Adiputra, Kirana Dara Dinanti; Sukandi, Sukandi; Sonjaya, Herry; Hasbi, Hasbi; Baco, Sudirman; Erni, Nurliani (Journal of Agriprecision & Social Impact, 2025)
This study investigated the heat tolerance of horned and polled Bali cattle under high ambient temperatures and physical exercise using heat tolerance index parameters. Eight male Bali cattle (four horned and four polled) were observed in the morning and afternoon after walking exercises under direct sunlight. Measured parameters included the Iberian Heat Tolerance Coefficient (IHTC), Benezra’s Coefficient (BC), and panting score (PS). A 2×2 factorial design (cattle type × measurement period) was used, and data were analyzed via two-way ANOVA, followed by Duncan’s test for significant interactions (P < 0.05).Results showed no significant differences (P > 0.05) in heat tolerance indices between horned and polled cattle. IHTC (106.15 ± 9.89 vs. 102.40 ± 10.93), BC (2.22 ± 0.35 vs. 2.28 ± 0.39), and PS (0.88 ± 0.83 vs. 1.38 ± 1.06) were comparable, indicating similar physiological responses to heat. However, the measurement period significantly affected (P < 0.05) all parameters. IHTC decreased in the afternoon (96.78 ± 5.56) compared to the morning (114.78 ± 5.22), while BC (2.29 ± 0.76 vs. 1.91 ± 0.77) and PS (1.88 ± 0.64 vs. 0.38 ± 0.52) increased, suggesting cattle experienced heat stress as temperatures rose. significant interaction (P < 0.05) between cattle type and measurement period was observed. Horned cattle had the highest IHTC in the morning (117.70 ± 4.28), while polled cattle had the lowest in the afternoon (92.95 ± 4.25). Polled cattle also had the highest BC (2.64 ± 0.06) and PS (2.25 ± 0.50) in the afternoon, indicating greater heat stress susceptibility. In conclusion, while both types showed similar heat tolerance under normal conditions, polled cattle were more vulnerable to heat stress, particularly after physical exertion in the afternoon.